Media Flash Card dalam Peningkatan Penguasaan Mufrodat Bahasa Arab - Suhardi Suhardi; Enung Mariah; Abdul Kasim Achmad (Academic : Journal of Social and Educational Studies, 2023)
Abstract. This study aims to determine the planning, process and results of increasing mastery of mufrodat Arabic in learning Arabic using flashcard media. This type of research is Classroom Action Research (CAR). The subjects of this study were students of class VIII.A MTS Bontoramba with a total of 23 people. Data collection techniques used are test and observation techniques. This research consisted of 2 cycles and each consisted of 2 meetings. From the test data in the first cycle, the average student score was 66.4, and in the second cycle, the average value was 90.7. This shows that the use of flashcard media can improve the Arabic mufrodat mastery of class VIIIA MTS Bontoramba students with an increase of 24%. Results of observations of teacher activities at each meeting (P) in cycle I (P1 of 66.6 and P2 of 83.3), while in cycle II (P1 and P2 each of 100), and results of observations of student activities in cycle I (P1 was 50 and P2 was 83.3) while in cycle II (P1 and P2 were 100 each). The results of observations of teacher and student activities show that there was an increase in both teacher and student activities by 16.6%.Keywords: Media Flashcard, Mufrodat, Arabic